Participation and retention factors relating to Black reentry graduate and undergraduate women in the College of Education. - Juantia Johnson-Bailey; Angela Humphrey Brown (Adult Education Research Conference, 1997)
This qualitative study, which focused on participation and retention factors, examined the educational experiences of nine reentry Black women who were students at a predominately White research university. The research centered on extracting common themes and on identifying factors that influenced or hindered their educational tenure.